0010 Clarification and application of human factors and ergonomics in frontline healthcare. (2nd November 2015) - Woodier, Nick; Kwa, Adrian; Chambers, Malcolm; Barrow, Clare; Baxendale, Bryn
Abstract : Background: Human Factors and Ergonomics (HFE), although a term now more familiar, 1 remains poorly understood in healthcare. This is partially due to inadequate models that are too complex and not applicable, and a lack of engagement from frontline staff due to jargon-based terminology from other industries. 2 We aimed to create a new HFE model appropriate for frontline healthcare use; designed by frontline staff for use by frontline staff. Methodology: An initial model was devised by a medic with a background in clinical care. This model, based on a hierarchical structure, was disseminated to staff and students in various disciplines and environments for feedback. They were asked questions considering key model attributes based on published literature. 3 Feedback was used to create a final "onion" model considering the patient, individual staff, team, task (environment, protocols and equipment), organisation and government. This final model was shown to participants on a multiprofessional simulation day with a short education workshop and examples of its application in a simulation setting. Participants were asked to then apply it to their own clinical systems on return to their workplace and provide feedback. Results/outcomes (recorded to date): 15 multiprofessional staff and 10 students provided feedback identifying that the model was concise (92%), easy to understand (76%), easy to remember (68%) and applicable (96%). To date it has been shown to 32 medical and 8 nursing staff on the simulation day. They have been able to use the model in their own systems to identify such issues as: poor handover, difficult equipment and inhibitory environmental design. Potential impact: This model is well received and applicable to frontline healthcare for use by multiprofessional staff. It provides a clarification of the system-wide applications of HFE and allows identification of system issues for improvement practice. References: Human Factors in Healthcare. A National Quality Board concordat. November 2013 Civil Aviation Authority. Fundamental Human Factors Concepts. 2002. CAP 719 Sheridan TB. Evaluating models in systems ergonomics with a taxonomy of model attributes. Appl Ergon. 2014;45 :78e–84